Manajemen Kurikulum Berbasis Riset dalam Meningkatkan Mutu Lulusan di MA NU Al Mustaqim Bugel Jepara - Mohammad Nashih; Sukarman; Haryanto (Al-Idaroh: Jurnal Studi Manajemen Pendidikan Islam, 2026)
This study examines the implementation of research-based curriculum management and its impact on graduate quality at MA NU Al Mustaqim Bugel Jepara, an Islamic senior secondary school in Central Java, Indonesia. The increasing demands of higher education institutions and the labor market have placed substantial pressure on secondary schools to produce graduates who possess not only academic competencies but also research literacy and critical thinking skills. Research-based curriculum management represents an innovative educational approach that integrates inquiry-driven learning, evidence-based pedagogical practices, and systematic curriculum evaluation into school governance. This qualitative case study was conducted over five months with 23 participants including school principals, curriculum coordinators, teachers, and students, supplemented by document analysis and classroom observations. Triangulation of sources and member checking ensured data credibility. Findings reveal that MA NU Al Mustaqim has implemented a three-phased research-based curriculum management model encompassing planning, implementation, and evaluation stages. Key outcomes include measurable improvements in students' critical thinking dispositions, enhanced teacher professional competency through action research, increased graduate acceptance rates at reputable higher education institutions (34% through SNBP in 2023 compared to 18% in 2021), and stronger school accreditation performance. Challenges identified include limited research infrastructure, insufficient teacher training in research methodology, curriculum overload concerns, and the need for stronger stakeholder alignment. This study contributes to the growing literature on curriculum innovation in Indonesian Islamic secondary schools and offers practical implications for educational policymakers and school administrators seeking to enhance institutional quality through research-integrated governance frameworks.